INTEGRATION ISLAMIC VALUES OF MINDFULNESS IN PAI BASED ON DEEP LEARNING - Fitri Amalia Majid (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study explores the integration of Islamic mindfulness values into Deep Learning–based Islamic Religious Education (PAI) as a transformative pedagogical approach for strengthening students’ spiritual awareness and moral character in the era of globalization and digitalization. Islamic mindfulness is understood as an inherent dimension of Islamic spirituality rooted in tawhid consciousness and manifested through the practices of muraqabah, tafakkur, dhikr, and ihsan. The study aims to analyze the concept of mindfulness from an Islamic perspective, examine the characteristics of Deep Learning–based PAI, and formulate an integrative pedagogical framework that internalizes mindfulness values within the learning process. This research employs a qualitative library research method through the analysis of contemporary literature related to Islamic psychology, mindfulness studies, and Islamic education pedagogy. The findings reveal that Deep Learning based PAI emphasizes meaningful conceptual understanding, critical and reflective thinking, contextual integration between Islamic texts and real-life issues, higher-order thinking skills, and the transformation of values into authentic behavior. The integration of Islamic mindfulness produces a three-dimensional pedagogical framework consisting of: (1) a cognitive-reflective dimension through tafakkur to deepen students’ understanding of Islamic teachings; (2) an affective-spiritual dimension through muraqabah to cultivate awareness of Allah’s presence in the learning process; and (3) a practical-ethical dimension that transforms Islamic values into concrete daily actions, including in digital environments. This integrative model contributes to strengthening students’ spiritual resilience, self-regulation, and moral awareness, while promoting a reflective, contextual, and value-oriented paradigm of Islamic education that is relevant to contemporary educational challenges.